The color of the skin. 1. Hypomelanosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Diseases of very different severity and frequency are included in this chapter. Ash-leafshaped hypomelanotic macules of tuberous sclerosis are rare. However, they are often the earliest sign of the disease. Vitiligo is less rare and is important due to esthetic and psychological reasons. After puberty hypochromic pityriasis versicolor is very frequent. However, it practically does not exist in children. Hypochromic sequelae of traumas or other dermatoses, mainly atopic dermatitis, are most frequent in children, especially in summer and autumn. (...).